A conditional probability index to quantify the amplitude and the direction of spatiotemporal changes in communities. Issue 4 (12th April 2017) - Sylvain, Jean‐Daniel; Drolet, Guillaume; Thiffault, Nelson; Beguin, Julien; Hébert, François
Abstract: Monitoring and mapping species diversity using indicators can allow the detection of changes in communities. Conclusions regarding these changes greatly depend on the choice of indicator. Here, we propose a new metric, the distance biochange index ( D BCI ), that enables the characterization and quantification of both the level and direction of change in biological communities relative to a given reference state. The proposed metric uses conditional probabilities to assess the probability of observing a complete change in a given community and can be decomposed into four conditional probabilities of change: no change, complete change in species composition only, complete change in species richness only, and complete change in both species composition and richness. In this study, we compared the properties of D BCI and BCI, a similarity version of D BCI, with those of other widely used indices. We also proposed a new approach, based on the use of partial derivatives, to assess the sensitivity of six similarity indices over a wide range of contrasting scenarios of change. Finally, we extended the application of D BCI to a simulated case study of the predicted evolution of suitable habitats for 20 species under climate change. Results from this simulation demonstrated that D BCI provides an accurate assessment of the level and direction of change. Results also show that D BCI can be used to reflect the effect of ecological gradients on species composition and species richness in biological communities.